Simulation analysis of models for estimation of empty travel time of vehicles in non-automated material handling systems - Dukić Goran; Opetuk Tihomir; Cajner Hrvoje; Jakovljević Matko (FME Transactions, 2018)
In designing or redesigning a facility like manufacturing plant or warehouse, an integral part is a proper selection of material handling system. Despite large alternatives, including automated material handling systems with conveyors or automated guided vehicles, most facilities today use for material handling man-driving vehicles (non-automated discrete material handling system). Proper design of such systems requires determination of required number of vehicles. Determination of empty vehicle travel time is based on either time consuming simulation or nonsimulation approach using estimation. The main goal of this paper is to review and analyse some proposed methods for empty travel time estimation of non-automated discrete material handling systems. Results obtained by estimation methods are compared with the simulation results.